INFLUENCE OF BIOLOGICAL PRODUCTS ON THE YIELD OF SOWING MILLET IN ORGANIC PRODUCTION - Столяр, Світлана; Трембіцька, Оксана; Білоцерківська, Лілія; Самков, Владислав (SWorldJournal, 2024)
The study considers the urgent problem of increasing the productivity of sowing millet under conditions of organic production. Theoretical analysis and experimental studies have shown that the use of biological products is an effective tool for achieving